Sintesis dan Karakterisasi Kalsium Karbonat Presipitat dari Limbah Cangkang Telur melalui Metode Karbonasi - Sekaringgalih, Ratri; Laili Rachmah, Alif Nur; Raharjo, Sonya Hakim; ., Ansori (Rekayasa Material, Manufaktur dan Energi, 2025)
Precipitated Calcium Carbonate (PCC) is a synthetic form of calcium carbonate (CaCO₃) with a dominant calcite crystal structure, widely used in various industrial applications such as fillers in the paper, plastic, paint, and pharmaceutical industries. This study aims to synthesize PCC from chicken eggshell waste through the carbonation method and determine the optimum conditions based on variations in sulfuric acid (H₂SO₄) concentration and carbonation time.The synthesis process begins with a reaction between eggshell powder and H₂SO₄ solution to produce calcium sulfate (CaSO₄), which is then converted into a Ca(OH)₂ solution through dissolution and precipitation. This solution is subsequently carbonated using CO₂ gas to produce PCC precipitate. Variations in H₂SO₄ concentration used were 1 M, 1.5 M, and 2 M, while the carbonation times were 60, 75, and 90 minutes. The synthesized PCC was characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray fluorescence (XRF), and X-ray diffraction (XRD).Based on the analysis results, the optimum condition was achieved at 2 M H₂SO₄ concentration and 90 minutes of carbonation. Under these conditions, XRD analysis showed a diffraction pattern characteristic of calcite as the dominant crystal form, while FTIR analysis exhibited sharp absorption peaks of the carbonate group (CO₃²⁻) in the range of 1400–870 cm⁻¹, indicating a high CaCO₃ content in the sample. XRF analysis confirmed a calcium content of 89.88% in the resulting PCC product. These results demonstrate that chicken eggshell waste has great potential as an environmentally friendly alternative raw material for the production of PCC using the carbonation method.Keywords: Precipitated Calcium Carbonate (PCC), eggshell, carbonation method, H₂SO₄